Refractive Outcomes of Retropupillary Fixated Iris-Claw Lens for Exchange of the Dislocated Intraocular Lens Using Modified Scleral Incisions - Kim H (Dove Medical Press, 2021)
Hyungil Kim,1 Sohee Jeon2 1Gyeongju St. Mary’s Eye Clinic, Gyeongju-si, Gyeongsangbuk-do, Republic of Korea; 2Keye Eye Center, Seoul, Republic of KoreaCorrespondence: Sohee JeonKeye Eye Center, 326 Teheran-ro, Gangnam-gu, Seoul, KoreaTel +82-02-6207-1236Fax +82-02-6207-1246Email soheeeee@gmail.comPurpose: To evaluate refractive outcomes after retropupillary iris-claw intraocular lens (IOL) implantation and to compare postoperative astigmatism from (1) a conventional 5.5-mm sclerocorneal incision, (2) an L-shaped scleral tunnel incision, and (3) a frown scleral tunnel incision.Methods: This was a retrospective study of eyes undergoing dislocated IOL exchange for a retropupillary iris-claw IOL. Uncorrected and corrected distance visual acuity (UDVA and CDVA) and postoperative complications were evaluated until postoperative months 24. The refractive outcomes and the surgically induced astigmatism (SIA) vector were compared between groups.Results: The medical records of 107 eyes from 107 patients with mean age of 65.31 ± 12.15 years were reviewed. Eyes with a frown incision showed the best UDVA, followed by those with L-shaped and conventional incisions (P = 0.003). Eyes with an L-shaped incision or frown incision had a lower SIA than that of the conventional incision group at postoperative 6 months (mean ± standard deviation [SD] SIA, 0.86 ± 0.85 D, 0.63 ± 0.37 D, and 1.70 ± 1.27 D for frown incision, L-shaped incision, and conventional incisions, respectively; P = 0.004).Conclusion: The frown incision and L-shaped incision induced a significantly smaller SIA than the conventional incisions, which was associated with better UDVA postoperatively.Keywords: aphakia, astigmatism, intraocular lens dislocation, retropupillary iris-claw intraocular lens, scleral tunnel incision, sclerocorneal incision